Information-seeking in mice (Mus musculus) during visual discrimination: study using a distractor elimination paradigm - Yuya Hataji; Kazuhiro Goto (Animal Cognition)
Abstract Some animals seek information to solve problems when they do not know the answer. Information-seeking behavior has become a key focus in studies of animal metacognition, providing insights into how animals monitor their own knowledge states. This behavior is thought to be a form of metacognitive control. Nevertheless, research on such metacognitive control has been biased toward specific taxa, such as primates, and has not been conducted in rodents, which are the most common experimental animals. This study examined whether mice exhibit information-seeking behavior during two visual discrimination tasks and what factors influence this behavior. We trained mice to discriminate between stimuli differing in luminance or orientation, with more minor differences increasing task difficulty. An information-seeking option was introduced during these tasks, allowing mice to eliminate distractor stimuli and ensure a correct response. The results indicated that mice sought information more frequently during difficult discriminations than easier ones. However, subsequent generalization tests revealed that the mice relied on environmental cues to utilize the information-seeking option. These findings suggest that information-seeking behavior in mice may not solely reflect metacognitive processes, and further investigation is needed to explore alternative explanations.